Analisa Pemilihan Bacaan Imam dalam Salat di Masjid Muhammadiyah Kota Palopo - Julianto, Teguh Arafah; Rukman Abdul Rahman Said; Zuhri Abu Nawas; Baso Fadhil Anugrah (Program Studi Ilmu Al-Quran dan Tafsir, 2024)
Abstract: This research discusses the Analysis of Imam's Recitation Selection in Prayer at Muhammadiyah Mosque in Palopo City. This research aims to: 1) Identify the recitations commonly chosen by imams in prayer in Muhammadiyah-assisted mosques, 2) Analyzing the factors that influence the selection of prayer readings, 3) Investigating the diversity in the selection of imam readings in prayer in Muhammadiyah mosques in Palopo City. The type of research used in this study is qualitative research with case study method. From the results of the research on the Analysis of the Selection of Imam's Recitation in Prayer in Muhammadiyah Mosques in Palopo City, it shows that: 1. The imams of al-Khaeriyyah, al-Awwabin, and Nurul Ilmi mosques read short surahs at maghrib time, such as surahs, al-Nas, al-Falaq, al-Ikhlas, al-Kafirun, al-Nasr, al-Kautsar, al-Fil, Qurasy, al-'Asr, and al-Ma'un. While at Isha time the Imams read the medium surahs such as al-'Alaq, al-Zalzalah, al-Bayyinah, al-Duha', al-Qari'ah, al-Baqarah. While at Fajr the Imams read medium and long surahs such as, al-Ghasyiah, al- A'la, al-Bayyinah, al-Zalzalah, al-Adiyat, al-Nazi'at, al-Naba', al-Mulk, Yasin, al-Isra and al-Baqarah. 2. The factors that influence the reading are due to following the sunnah, meaning and content and looking at aspects of the condition of the congregation, 3. The imams of the Muhammadiyah-assisted mosque have readings that are not uniform.